PENGARUH FASILITAS, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN NGGONE KONCOKU COFFE HOUSE DI SURAKARTA (Survei pada Pelanggan Nggone Koncoku Coffe House di Surakarta) - Nofitasari, Alwi Suddin & Rahayu Triastity (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aims to analyze (1) the effect facilities on consumer satisfaction Nggone Koncoku Coffe House in Surakarta. (2) the effect of service quality on customer satisfaction Nggone Koncoku Coffe House in Surakarta. (3) the effect of price on consumer satisfaction Nggone Koncoku Coffe House in Surakarta. (4) the dominant variable influence on consumer satisfaction Nggone Koncoku Coffe Huse in Surakarta. The study population was the whole kosumen Nggone Kocoku Coffe House with a sample of 100 respondents. Data collection technique used questionnaire that through stages of testing the validity and reliability first. Test requirements regression using classic assumption test. Data were analyzed using multiple linear regression. The conclusion of each hypothesis test results show that (1) the facility significantly influence consumer satisfaction Nggone Koncoku Coffe House in Surakarta, evidenced from t test that generates a probability value (0.003)<0.05. (2) quality of service significantly influence consumer satisfaction Nggone Koncoku Coffe House in Surakarta, evidenced from t test that generates a probability value (0.011)<0.05. (3) The price does not significantly influence consumer satisfaction Nggone Koncoku Coffe House in Surakarta, evidenced from t test that generates a probability value (0.794)>0.05. The conclusion of this study that the entire hypothesis can be accepted or proven true, unless the price of consumer satisfaction Nggone Koncoku Coffe House in Surakarta. Based on these results, maintaining customer satisfaction is very important in marketing strategies. With consumer satisfaction, consumers will be loyal to the products and services sold.Keywords: facilities, service quality, price, customer satisfaction